Rynetta Dress: Integrating Traditional Accents into Contemporary Party Wear - Auryndhani Salsabila; Anggita Prameswari; Sri Endah Wahyuningsih; Kezia Natali (Universitas Negeri Semarang, 2026)
Party wear is a fashion product that continues to develop in response to the increasing demand for formal attire that not only serves functional purposes but also reflects aesthetic value and cultural identity. This study aimed to create a women's party dress entitled Rynetta Dress, which integrates traditional elements and embellishments into a modern design. The study employed a creative research method consisting of design planning, pattern making, fabric cutting, sewing, garment structure installation, and decorative finishing. The main materials used were satin fabric combined with lining, tricot, boning, beads, pearls, and floral appliqués as decorative elements. The result is a women's party dress featuring an I-line silhouette and a mermaid-style skirt that creates an elegant and feminine appearance. The uniqueness of the design lies in the use of a detachable bolero with patterned fabric accents on the shoulder area as the garment's focal point, complemented by embellishment details that enhance its aesthetic value. The results indicate that the product demonstrates compatibility between the design concept, material selection, construction techniques, and the characteristics of the target users, namely women aged 20–35 years. This work is expected to serve as an alternative reference for developing party dress designs that harmoniously combine modern and traditional elements. Keywords: party dress, traditional elements, embellishment, fashion design, Rynetta Dress